SCHOOL PRINCIPALS’ MANAGERIAL AND LEADERSHIP IN 3T REGIONSMANAJERIAL DAN KEPEMIMPINAN KEPALA SEKOLAH DI DAERAH 3T - Ismadi Ismadi; Amiruddin; Yeni Marlina; Masyitah (Lembaga Sepercenter, 2026)
Introduction. This study examines the managerial practices and leadership styles of school principals in 3T areas (frontier, outermost, and disadvantaged) in Indonesia, where geographical, infrastructural, and human resource challenges significantly impact the quality of education. Research Methods. This research employed a qualitative approach with a multiple case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving eight school principals and 24 teachers from four provinces classified as 3T regions (Papua Barat, Nusa Tenggara Timur, Maluku Utara, and Kalimantan Utara) in 2024–2025. Data Analysis. Data were analysed using thematic analysis with open, axial, and selective coding assisted by NVivo 14 software. Results. The findings reveal that principals in 3T areas predominantly apply a blended managerial-leadership style: (1) adaptive-transformational leadership to motivate teachers; (2) resource-based managerial practices by maximising limited facilities and community involvement; and (3) situational decision-making oriented towards teacher welfare and student access. The main challenges include teacher turnover, inadequate infrastructure, and difficult internet access. Conclusion. Effective principals in 3T areas succeed by combining strong personal character, cultural approaches, and collaborative networks with local governments and communities. This study proposes the “Adaptive Contextual Leadership” model for school principals in disadvantaged areas.